Change in Contemporary South Africa - Thompson, Leonard (University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1975.
Keywords: South Africa -- Politics and government -- 1961-1978.; South Africa -- Social conditions -- 1961-1994.; South Africa -- Race relations.; South Africa -- Social conditions.; Afrique du Sud -- Politique et gouvernement -- 1961-1978.; Afrique du Sud -- Conditions sociales -- 1961-1994.; Afrique du Sud -- Relations raciales.; Afrique du Sud -- Conditions sociales.; Politics and government.; Race relations.; Social conditions.; South Africa.; 1961-1994